De libros clandestinos y nigromantes: en torno a la posesión y transmisión de grimorios en dos procesos inquisitoriales entre 1509 y 1511 - Pedraza García, Manuel José (Revista General de Información y Documentación, 2007)
The use of prohibited books in Spain in the 16th century, grimoires specially, is considered. Two processes for necromancy of the Spanish Inquisition in Zaragoza in 1509 an 1511 are presented. From these processes the production and transmission of grimoires are analysed.